How Do Learners Interact with Photos, Graphics, and Maps in Geography Textbooks while Completing a Learning Task? - Behnke, Yvonne (Journal of Geography Education, 2023)
This paper presents the results of an eye-tracking study accompanied by a questionnaire investigating learners’ visual information selection of textbook elements while completing two tasks. Data from 58 students (14–17 years) were analyzed. The study revealed that participants who successfully completed the tasks also selected relevant information effectively and efficiently. Among other things, they considered relevant text and integrated relevant images into task-processing. The study provides insights into current Geography textbooks and their usability (challenges) regarding photos, graphics, and map usage to construct geographical knowledge and elaborates optimization potential regarding image usability and a learning supporting integration of images and tasks.